SDG'S IN FAMILY LAW: THE EFFECT OF GENDER INEQUALITY ON THE QUALITY OF CHILDREN'S EDUCATION IN THE FAMILY - Turnip, Luisa Oktaviana; Judiasih, Sonny Dewi; Yuanitasari, Deviana (Ajudikasi : Jurnal Ilmu Hukum, 2024)
Men and women based on the influence of social culture of society (social construction) by not looking at biological types in equality. Gender differences, which in turn give birth to gender roles, are actually not a crucial problem, as long as they do not cause gender inequalities. However, the reality in society shows that gender differences have created various forms of inequality or injustice, both for men and especially for women. Equal and fair gender relations between parents related to child care and education in the family affect the quality of children's education. So far, the role of women (mothers) in assisting children's education is more than men. School selection and other education are often delegated to women. Family law can also influence the educational priorities of girls and boys. Some cultural norms may direct boys to get a better education than girls, which ultimately impacts on their future employment opportunities and quality of life. In addition, family law also plays a role in determining employment opportunities for women. In Indonesia, there are significant differences in employment opportunities between men and women. Traditional norms and practices still restrict women from engaging in formal employment, especially after marriage or having children. This is closely related to family law provisions that assign women traditional roles as mothers and housekeepers. This research is an empirical-normative legal research. The results of this research state that: First, that in a society with a patrilineal kinship system in a neighborhood in Medan there is still a low level of understanding and implementation of gender equality. Second, the gender inequality that still occurs especially in patrilineal societies affects the quality of education that is unequal between genders and worsens the quality of education and labor in Indonesia. In Indonesia, there are significant differences in employment opportunities between men and women. Traditional norms and practices still restrict women from engaging in formal employment, especially after marriage or having children. This is closely related to family law provisions that assign women traditional roles as mothers and housekeepers..